Energy and exergy analysis of a PV-T integrated ethanol PEM electrolyzer. (6th April 2021) - Caglar, Basar; Araz, Mustafa; Ozcan, Huseyin Gunhan; Calisan, Atalay; Hepbasli, Arif
Abstract: A photovoltaic-thermal (PV-T) integrated ethanol proton exchange membrane electrolyzer (PEME) was proposed as a low-energy consuming energy storage option for renewable-sourced electricity as well as a way for simultaneous chemical production in this study. Energy and exergy analyses were applied to each component of the system (e.g., pumps, heat exchanger, PV-T, PEME, and separation unit (SPU)) and the whole system to assess the system performance. The mathematical modelling of the whole system along with its main components except for the SPU was done using the Engineering Equation Solver (EES) software package while the SPU was modelled through the ASPEN Plus. A detailed modelling of the PEME was also included. The effects of the PV-T and PEME parameters on energy and exergy efficiencies of the system were evaluated while the improvement potentials and scale up options were discussed. Energy and exergy efficiencies of the proposed system at the optimum operation of the PEME and under average climatic conditions in the city of Izmir, Turkey were determined to be 27.8% and 3.1%, respectively. Energy and exergy efficiencies of the system were mainly regulated by the PV-T and PEME, whose energy and exergy efficiencies were 40.6%, 56.6% and 13.8%, 14.1%, respectively. Effective PEME parameters for energy and exergy efficiencies of the system were membrane conductivity, membrane thickness, anode catalyst and the operation temperature of the PEME. By changing the PV-T and PEME parameters and by scale-up, energy and exergy efficiencies of the system could be improved. Graphical abstract: Image 1 Highlights: A PVT integrated ethanol proton exchange membrane electrolyzer (PEME) was proposed. A detailed mass transfer modelling of the ethanol PEME was developed. The energy and exergy efficiencies of the system are 27.8 and 3.1%, respectively. Total energy and exergy consumptions in off-grid mode are 997.4 and 767.1 MJ/kg. Maximum energy and exergy efficiencies by scale-up are 35 and 10%, respectively.